The use of stress test in patients after coronary artery bypass grafting to assess the effectiveness of surgery, determination of rehabilitation possibilities and prognosis - A. A. Inozemtseva (Бюллетень сибирской медицины, 2018)
The review provides the data on current approaches on the use of stress tests to determine the programs, rehabilitation terms and the prognosis in patients who have undergone coronary artery bypass grafting (CABG). The experience of foreign and Russian clinics shows the necessity and relevance of stress testing in this category of patients. However, currently there are no clear recommendations on the terms and methods of stress testing in patients who underwent CABG. The widespread introduction of stress testing in general and spiroveloergometry in particular into practical medicine will allow for the production of personalized training programs and for the evaluatation of the patient’s prognosis, rehabilitation and labour potential.